2005
DOI: 10.1111/j.1447-073x.2005.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

A cadaver with azygos lobe and its clinical significance

Abstract: Although an azygos lobe is a rare anomaly of the lung, its radiological appearance has been well defined. Clinically, the azygos lobe has been accepted as a normal variation that can simulate various diseases. However, on chest roentgenograms, this anomaly may appear to be present if there are any other pathological conditions. So, the detection of this anomaly and clarification of its precise anatomical features are important not only to differentiate this anomaly from other pathological conditions, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Numerous investigators have reported on the azygos lobe of the human lung (Stibbe, 1919;Cairney, 1923;Cohen and Dooneief, 1951;Boyden, 1952;Kolbenstvedt et al, 1979;Kobayashi et al, 1995;Cimen et al, 2005;Hirose and Cowles, 2007). However, most of these reports were based on X-ray radiography and modern methods of clinical imaging and, therefore, contained little anatomic descriptive detail about the bronchus and pulmonary vessels distributing to the azygos lobe.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous investigators have reported on the azygos lobe of the human lung (Stibbe, 1919;Cairney, 1923;Cohen and Dooneief, 1951;Boyden, 1952;Kolbenstvedt et al, 1979;Kobayashi et al, 1995;Cimen et al, 2005;Hirose and Cowles, 2007). However, most of these reports were based on X-ray radiography and modern methods of clinical imaging and, therefore, contained little anatomic descriptive detail about the bronchus and pulmonary vessels distributing to the azygos lobe.…”
Section: Discussionmentioning
confidence: 96%
“…However, anatomical evaluation of the branching pattern of the bronchial tree is important for physicians engaged in respiratory care and a detailed anatomical understanding of the bronchial branches in this lobe can facilitate appropriate respiratory care, particularly therapeutic postural drainage, for patients with this lobe. In previous anatomical reports of the azygos lobe in human autopsy cases (Stibbe, 1919;Cairney, 1923;Foster-Carter, 1946;Cimen et al, 2005;Bancroft and Stephens, 2007), partial removal of lung parenchyma to elucidate the branching pattern of the bronchial tree was unfortunately not done. Partial removal of the parenchyma, including the alveoli, the terminal bronchioles, and bronchial arteries and veins of the azygos lobe and associated areas of the lung, is crucial for investigating the detailed branching patterns of the bronchi in this lobe.…”
Section: Introductionmentioning
confidence: 95%
“…[ 2 ] It is commonly seen in males and has also been reported on the left side. [ 3 ] An azygos lobe is not susceptible to disease. [ 1 ] However, multiple authors have reported spontaneous pneumothorax associated within the azyos lobe in adult and pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 6 ] Clinically, the knowledge of azygos lobe anatomy is important during thoracic surgical approaches. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the azygos lobe is a variation that can simulate various diseases and is most often found incidentally during chest radiography or computed tomography (CT) [ 5 - 6 ]. Its radiographic appearance is that of a dense, comma-shaped shadow which begins at the apex of the right lung and curves downwards and inwards towards the mediastinum, ending a little below the level of the first costal cartilage [ 1 ].…”
Section: Introductionmentioning
confidence: 99%